Cloning and sequencing of the alkaline extracellular protease gene of Yarrowia lipolytica. - Davidow, L S (1987)
The XPR2 gene encoding an alkaline extracellular protease (AEP) from Yarrowia lipolytica was cloned, and its complete nucleotide sequence was determined. The amino acid sequence deduced from the nucleotide sequence reveals that the mature AEP consists of 297 amino acids with a relative molecular weight of 30,559. The gene codes for a putative 22-amino-acid prepeptide (signal sequence) followed by an additional 135-amino-acid propeptide containing a possible N-linked glycosylation site and two Lys-Arg peptidase-processing sites. The final Lys-Arg site occurs at the junction with the mature, extracellular form. The mature protease contains two potential glycosylation sites. AEP is a member of the subtilisin family of serine proteases, with 42.6% homology to the fungal proteinase K. The functional promoter is more than 700 base pairs long, allowing for the observed complex regulation of this gene. The 5' and 3' flanking regions of the XPR2 gene have structural features in common with other yeast genes.